2016
DOI: 10.1186/s12904-016-0112-9
|View full text |Cite
|
Sign up to set email alerts
|

Timely identification of palliative patients and anticipatory care planning by GPs: practical application of tools and a training programme

Abstract: BackgroundPalliative care is mainly restricted to terminal care. General practitioners (GPs) are not trained to early identify palliative patients with cancer, COPD or heart failure. With the help of the RADboud indicators for PAlliative Care needs (RADPAC), we trained GPs to identify patients’ needs and to make a proactive care plan. They were also able to join two role-plays where they discussed the patient’s future, and consulted a palliative care consultant to fine-tune the care plan. We evaluated the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…Like others, we found that GPs find it hard to identify and discuss palliative care needs with patients with organ failure [ 23 , 34 ]. Moreover, our finding that initiating ACP is difficult when patients are still being treated in hospital is also confirmed in other literature [ 35 37 ]. It was mentioned in our study that ‘it is not ideal to ask about their wishes when something happens, i.e.…”
Section: Discussionsupporting
confidence: 88%
“…Like others, we found that GPs find it hard to identify and discuss palliative care needs with patients with organ failure [ 23 , 34 ]. Moreover, our finding that initiating ACP is difficult when patients are still being treated in hospital is also confirmed in other literature [ 35 37 ]. It was mentioned in our study that ‘it is not ideal to ask about their wishes when something happens, i.e.…”
Section: Discussionsupporting
confidence: 88%
“…The ACP document consists of four separate single-page forms: (1) patient information including an overview of a patient’s advance directives; (2) an advance care plan stating anticipated future problems and an overview of all professional carers involved and how and when to contact them; (3) a current and recently discontinued medication overview and (4) a description of a patient’s current problems in all palliative domains: physical and care-related, social (including financial), psychological, and spiritual [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because of the availability nowadays of a range of palliative treatments (e.g. surgery, chemotherapy, immunotherapy, advanced heart failure therapy), patients are treated at the hospital longer than they used to be, falling outside of the scope of the general practitioner (GP), traditionally the doctor to deliver palliative care [ 19 21 ]. Moreover, palliative patients are identified as such earlier on in their disease process.…”
Section: Introductionmentioning
confidence: 99%
“…At first sight, this finding seems contradictory with existing data. Indeed, Thoonsen et al [ 6 , 51 , 52 ] have shown that training GPs makes them more easily able to discuss the future with their palliative patients, to identify more palliative patients and to provide multidimensional palliative care more often. Actually, these data are complementary since the training studied by Thoonsen et al aimed not only at providing knowledge but also skills and self-efficacy.…”
Section: Discussionmentioning
confidence: 99%